Why should I pay for e-books?: An empirical study to investigate Chinese readers' purchase behavioural intention in the mobile era. Issue 3 (5th June 2017) - Zhang, Min; Zhu, Mingxing; Liu, Xiaotong; Yang, Jun
Abstract : Purpose: Because mobile phones offer a new, affordable and easy-to-use portal to reading material, mobile reading is emerging as the most ultra-modern reading approach. From the perspective of mobile reading service providers, knowledge of customer purchase, and consumption behaviour is critical for their survival and success. This paper aims to provide insights into the factors that influence the purchase e-books. Design/methodology/approach: Following means-end chain theory, the prospect theory and elaboration likelihood model, a structural equation model is proposed to investigate and identify key factors that drive the purchase intention of experienced mobile readers. In the theoretical model, utilitarian value (UV) and hedonic value (HV) are supposed as formative second-order constructs formed by related payoff. Findings: Both UV and HV are positively associated with readers' purchase intention. However, there are no big differences between these two path coefficients. People seem to perceive relatively low payment risk although perceived risk could still negatively affect purchase intention. As a predictor of purchase intention, UV is less important when risk perception increases or when involvement (IV) decreases. Furthermore, this study illustrates that uniqueness and convenience (CV) are significant components of UV, whereas curiosity and flow are components of HV. Practical implications: Mobile reading providers should highlight the professional and specificity of app such as beautiful cover, page setup that similar to real books and so on. Readers should be allowed to post real-time reviews and communicate with others to improve their sense of satisfaction, participation and belonging. The payment process should be concise and simple through which readers can save their purchase time and effort. Mobile reading service providers should provide trustworthy payment approaches, especially third-party platform and guarantee the CV and safety of payment activity. Originality value: By focusing on the impacts of relationships among UV, HV, perceived risk and IV to purchase intention, this paper not only provides a theoretical understanding of mobile reading purchase behaviour but also offers practical insights to reading material manufactures and app developers for promoting such a process.